2020
DOI: 10.1016/j.molmet.2020.101083
|View full text |Cite
|
Sign up to set email alerts
|

Changes in circulating miRNA19a-3p precede insulin resistance programmed by intra-uterine growth retardation in mice

Abstract: Objective Individuals born with intrauterine growth retardation (IUGR) are more prone to cardio-metabolic diseases as adults, and environmental changes during the perinatal period have been identified as potentially crucial factors. We have studied in a preclinical model early-onset molecular alterations present before the development of a clinical phenotype. Methods We used a preclinical mouse model of induced IUGR, in which we modulated the nutrition of the pups durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 73 publications
2
13
0
Order By: Relevance
“…Interestingly, higher protein level of PTEN, one of the Akt activation inhibitors, was also found in livers of overfed 3-month-old males. In addition to this, significantly decreased levels of circulating miRNA19a-3p , a miRNA that acts to regulate PTEN, were found in both normally fed and overfed IUGR males ( 93 ). These finding hence suggests an association between altered epigenetic mechanisms and the risk of developing insulin resistance later in life of IUGR offspring.…”
Section: Intrauterine Growth Restriction and The Associated Altered E...mentioning
confidence: 83%
See 2 more Smart Citations
“…Interestingly, higher protein level of PTEN, one of the Akt activation inhibitors, was also found in livers of overfed 3-month-old males. In addition to this, significantly decreased levels of circulating miRNA19a-3p , a miRNA that acts to regulate PTEN, were found in both normally fed and overfed IUGR males ( 93 ). These finding hence suggests an association between altered epigenetic mechanisms and the risk of developing insulin resistance later in life of IUGR offspring.…”
Section: Intrauterine Growth Restriction and The Associated Altered E...mentioning
confidence: 83%
“…Interestingly, a major of the altered miRNAs are predicted to have a common target, which is methyl-CpG binding protein 2 ( 64 ). In a different study where F0 pregnant mice were fed a low-protein/calorie-deficit (-40%) diet from week 3 of gestation, and growth restricted pups were cross-fostered to 3 different groups right after birth, either normal milk feeding (6 pups/dam), overfed (3 pups/dam), or nutrition restriction (10 pups/dam), significantly reduced H3K4me3 (trimethylated histone H3 on lysine 4) region at the Akt1 gene, a gene that is known to play an important role in insulin resistance, was found in livers of 3-month-old IUGR males that either received normal milk feeding or were overfed, in association with reduced expression of Akt1 ( 93 ). Interestingly, higher protein level of PTEN, one of the Akt activation inhibitors, was also found in livers of overfed 3-month-old males.…”
Section: Intrauterine Growth Restriction and The Associated Altered E...mentioning
confidence: 99%
See 1 more Smart Citation
“…One such mechanism is miRs, which are small, non-coding RNA molecules that silence target genes through mRNA degradation or repressed protein translation. Numerous miRs have been demonstrated to have aberrant postnatal expression in growth-restricted offspring, leading to cellular stress that precedes impaired function of metabolic organs [ 51 , 86 , 87 , 88 ]. Recent studies found that the translation of p66Shc protein is directly inhibited by miR-203a-3p, leading to the attenuation of liver injury and fibrosis in mice [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…One such mechanism is miRs, which are small, non-coding RNA molecules that silence target genes through mRNA degradation or repressed protein translation. Numerous miRs have been demonstrated to have aberrant postnatal expression in growth-restricted offspring, leading to cellular stress that precedes impaired function of metabolic organs [51,[86][87][88]. Recent studies have found that the translation of p66Shc protein is directly inhibited by miR-203a-3p, leading to the attenuation of liver injury and fibrosis in mice [56].…”
Section: Discussionmentioning
confidence: 99%